Effect of no treatment, cimetidine 1 g/day, cimetidine 2 g/day and cimetidine combined with atropine on nocturnal gastric secretion in cimetidine non-responders. Issue 11 (November 1984) - Gledhill, T; Buck, M; Hunt, R H
Abstract : We have studied nocturnal acid secretion in patients with duodenal ulcer who met predetermined criteria of poor clinical response to cimetidine. Different groups of patients were investigated receiving either no treatment, cimetidine 1 g/day, cimetidine 2 g/day or cimetidine 1 g/day combined with atropine 4.8 mg/day. The results were compared with those obtained from other patients with duodenal ulcer who were studied in our department but who were not classified as according to their clinical response to cimetidine. The results show that despite adequate absorption, cimetidine has a decreased effect at controlling acid secretion in the poor responders and that increasing the dose of drug does not improve response. Control of acid output was, however, dramatically improved when cimetidine was combined with atropine which suggests that patients who do not respond to H2-receptor blockade should be treated by a combination of cimetidine with an anticholinergic agent.